Survei Keterampilan Teknik Dasar Futsal Pada Pemain Klub Bunga Kenanga FC Kota Bengkulu - Hermawati, Herli; Sumantri, Ajis; Asnawati, Asnawati (UNIVED Press, Universitas Dehasen Bengkulu, 2024)
This study aims to determine the level of skill of basic futsal techniques in Bunga Kenanga Fc club players Bengkulu City. This type of research is quantitative descriptive research. The research sample totalled 15 people. The instruments used in this study are basic techniques in futsal games which include Passing Controlling, Dribbling and Shooting tests. Where the overall results are as follows: from a total of 15 samples studied, the results of the basic techniques of futsal games were obtained (40%) had a deficient category. (42%) has a medium category. (9%) has a good category. (9%) has a very good category.